2022
DOI: 10.3389/fmolb.2022.991425
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive molecular analyses of an autoimmune-related gene predictive model and immune infiltrations using machine learning methods in moyamoya disease

Abstract: Background: Growing evidence suggests the links between moyamoya disease (MMD) and autoimmune diseases. However, the molecular mechanism from genetic perspective remains unclear. This study aims to clarify the potential roles of autoimmune-related genes (ARGs) in the pathogenesis of MMD.Methods: Two transcription profiles (GSE157628 and GSE141025) of MMD were downloaded from GEO databases. ARGs were obtained from the Gene and Autoimmune Disease Association Database (GAAD) and DisGeNET databases. Differentially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 78 publications
0
8
0
Order By: Relevance
“…This finding suggests a notable immune response specific to MMD, highlighting the potential role of immune mechanisms in the pathology of the disease [10]. Additionally, a close association was observed between dysregulated genes in MMD and genes related to autoimmune diseases [11]. Concerning peripheral immunity in MMD, previous single-cell sequencing has suggested that the interaction of peripheral immune cells may play a role in the pathogenesis of MMD [12].…”
Section: Introductionmentioning
confidence: 65%
“…This finding suggests a notable immune response specific to MMD, highlighting the potential role of immune mechanisms in the pathology of the disease [10]. Additionally, a close association was observed between dysregulated genes in MMD and genes related to autoimmune diseases [11]. Concerning peripheral immunity in MMD, previous single-cell sequencing has suggested that the interaction of peripheral immune cells may play a role in the pathogenesis of MMD [12].…”
Section: Introductionmentioning
confidence: 65%
“…This includes identifying differentially expressed genes (DEGs) and immune complexes. The study also found that gene-miRNA interactions play a role in modifying protein expression during disease progression by targeting specific factors [37].…”
Section: Pathophysiology Of Moyamoya Diseasementioning
confidence: 81%
“…They have the potential to be diagnostic biomarkers for MMD. Among them, PTPN11 showed a low expression pattern and the highest diagnostic accuracy, and it also showed the highest degree according to PPI network analysis, which was identified by Li et al (2022) , as aforementioned. PTPN11 encodes a non-receptor tyrosine phosphatase with 2 Src-homology 2 domains (Shp2) as well, and it was identified as the first proto-oncogene.…”
Section: Discussionmentioning
confidence: 96%
“…However, there is still no well-recognized biomarker for accurately diagnosing and predicting the outcome of MMD. CD38, PTPN11, NOTCH1, TLR7, KAT2B, and ISG15 were identified using machine learning, and a reliable diagnostic model was developed by Li et al (2022 ). Except RNF213, UNC13D was previously identified as a key biomarker with good specificity and sensitivity ( Jin and Duan, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation